Mismatch, forced disappearance and allegorization in 'Rubrica', a short-story by Caio Fernando Abreu - Franco, Arnaldo [UNESP] (Universidade Estadual de Maringa, 2022)
In this article, I analyze 'Rubrica', a short-story by Caio Fernando Abreu, originally published in the book Pedras de Calcutá, in 1977. It is one of the first texts in Brazilian literature to address the forced disappearances, that happened during the 1970s, through a scene that basically pictures a tense dialogue between a young man and a girl who approaches him to talk. In my reading, I discuss the relationship between the thematization of disappearances and the formal procedures to build a narrative, namely: the truncated dialogue, the figure-ground perception, the incorporation of procedures from the cinematographic narrative (zoom, cut, image juxtaposition, editing) and allegory. The resulting analysis highlights that the formal resources articulate themselves with the thematization to create a critical allegory of Brazil under the civil-military dictatorship.
Desencontro, desaparecimento forçado e alegorização em 'Rubrica', conto de Caio Fernando Abreu
Keywords: cinematographic language; civil-military dictatorship; short-story; violence